FRESCO–2 trial and fruquintinib: A clearer picture of the control arm - Sruthi Ranganathan; Alyson Haslam; Timothée Olivier; Vinay Prasad (Translational Oncology)
Though vascular endothelial growth factor receptor (VEGFR)-targeting drugs have been approved in the past and are known for their potential off-site action, fruquintinib is a possible new, specific inhibitor of VEGFR-1, 2, and 3. The US Food and Drug Administration (FDA) recently approved fruquintinib based on the FRESCO-2 trial results. However, the FRESCO-2 trial is potentially problematic given the suboptimal choice of placebo in the trial, and the poor cost-effectiveness of fruquintinib. Firstly, we argue that fruquintinib should have been tested against regorafenib, and only offered a moderate benefit despite being tested against a suboptimal placebo. Secondly, fruquintinib is likely cost ineffective (measured in quality-adjusted life years (QALY)), with a crude estimation placing its value over a million USD per QALY. Lastly, we show that the use of a suboptimal placebo is unfortunately not new.